Breaking boundaries: traditional unions in Serbia and the fight for gig worker rights - Jakobi, Tatjana (Sociološki pregled, 2025)
This paper highlights the barriers faced by Serbian trade unions in organizing platform workers and adapting to new forms of work. Using qualitative methods, it explores the normative, regulatory, and cultural-cognitive challenges in defining the status of platform workers in the absence of a clear legislative framework regulating platform work. The results empirically support Kathleen Thelen’s thesis on the impact of socio-economic factors and the potential for coalition-building on institutional change. The paper emphasizes the need for legislative reforms to clearly define the status of platform workers and create space for unions to adapt to technology-driven changes in the nature of work.
Keywords: platform economy; trade unions; regulatory frameworks; labor relations; legal barriers